حدود معاملة الأخوة والصحبة في الإسلام - Nurul Najwa Bt Muhammad Arifin@Rifin; نور النجوى محمد عاريفين@ريفين (Kolej Universiti Islam Malaysia, 2022)
The title of this research is" The limitations of relationship ukhwah and friendship in Islamic perspective". This research is divided to three parts. The methods for this research are from the library research and the internet. The purpose is to describe about the limitations in ukhwah and friendship in Islamic view. As we know, the ukhwah and friendship just is not only between muslim society but it also includes with the non- muslims. Based on the ukhwah and friendship, muslims and non- muslims have their own limitations. So, we must give respect to the limitations for a peaceful life.